2004
DOI: 10.1002/joc.1077
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal to interannual variations of soil moisture measured in Oklahoma

Abstract: Agriculture is a $2 billion component of the state economy in Oklahoma. As a result, meteorological, climatological, and agricultural communities should benefit from an improved understanding of soil moisture conditions and how those conditions vary spatially and temporally. The Oklahoma Mesonet is an automated observing network that provides realtime hydrometeorological observations at 115 stations across Oklahoma. In 1996, sensors were installed at 60 Mesonet sites to provide near-real-time observations of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
62
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 36 publications
8
62
0
1
Order By: Relevance
“…Soil moisture recharge occurs during the winter months. These patterns are similar to those reported by Illston et al (2004). There is relatively little intra-annual variation in mean monthly CV, although soil moisture at 5 cm is consistently more variable than at 25 and 60 cm.…”
Section: Study Regionsupporting
confidence: 86%
See 2 more Smart Citations
“…Soil moisture recharge occurs during the winter months. These patterns are similar to those reported by Illston et al (2004). There is relatively little intra-annual variation in mean monthly CV, although soil moisture at 5 cm is consistently more variable than at 25 and 60 cm.…”
Section: Study Regionsupporting
confidence: 86%
“…Figure 8a also shows a marked drop in NS between February and April, with an NS < 0.3 in March. Illston et al (2004) observed four distinct seasonal soil moisture regimes in Oklahoma. The transition between the first regime and second regime (February-April) is characterized by the initiation of 5 cm soil moisture drying beginning in mid-March, while 25 cm soil moisture drying does not initiate until early-to-mid April.…”
Section: Overall Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Doing so will help to quantify whether the plant seasonal cycle is modified by WFs. For example, during the peak growing season in JJA when SM is mostly limited due to higher temperatures and lower rainfall [44], the WT-enhanced vertical mixing may accelerate the SM deficit and thus inhibit vegetation growth due to enhanced ET, while during the vegetation greenup period when SM is adequate, the WT-enhanced vertical mixing may benefit plant growth. Such analysis will reveal whether there are noticeable changes in the plant seasonal cycle and whether the timing of such changes is due to the operating WTs.…”
Section: Detection and Attribution Methodsmentioning
confidence: 99%
“…Characteristic soil hydrological features for vegetation periods in temperate latitudes are a high initial soil water content in spring due to residual water from winter precipitation (snow and ice melt), a comparably dry summer season, and a rewetting of soil in fall (Illston et al 2004). This shape of a typical course of water content in soil will be referred to as the Bsinusoidal annual cycle.^It is mainly caused by meteorological characteristics in mid-latitude areas and modified by soil physical properties and vegetation.…”
Section: General Temporal Dynamicsmentioning
confidence: 99%